Analysis of Elements in Posters of Indonesian Children’s Animated Films - Chitta, Febyana; Ekawardhani, Yully Ambarsih; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The poster for the film Jumbo features characters from the film as well as the rural setting that serves as the story’s primary backdrop, such as the use of soft colors and environmental backgrounds that depict the daily lives of the village community. These elements serve as a visual representation of the film, helping to shape the audience’s initial perception of the atmosphere and values the film aims to convey. The objective of this study is to analyze the aesthetic elements of the animated film Jumbo poster using a method with the theory of aesthetic elements proposed by A.A.M Djelantik. This research reveals that the form (shape) of the poster displays character illustrations with a chibi cartoon illustration style, supported by a centered composition, clear visual hierarchy, and asymmetrical balance that creates a stable and harmonious impression. In terms of weight (content), this Jumbo animation poster presents a cheerful atmosphere and a spirit of adventure as seen from the happy and enthusiastic facial expressions of the characters and the use of other visual elements that convey a message of togetherness. In the appearance (presentation) aspect, the poster of the animated film Jumbo is presented attractively with good visual quality, lighting, and a communicative layout. In conclusio, these three aspects are interrelated in creating aesthetic value and effectively conveying the film’s message, contributing to the development of visual communication design particularly in film poster design.